Child Education Concept from The Perspective of Qira’ah Mubadalah - Abdullah Ahzami; Mistura; Putri Nisfi Siagian; Ade Naelul Huda (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2024)
The Holy Quran teaches universal values that are not limited to a specific race or gender. Allah, the Exalted, created humans in pairs to foster mutual understanding between them. Similarly, parental responsibility for child education should not be delegated to one party alone while the other remains indifferent. Among the societal phenomena is the stigma that the father's duty is solely to provide financially, while child education is entirely the mother's responsibility. Child education is considered a parental responsibility that encompasses various aspects, including faith, morals, physical, and social aspects. The concept of equality or